Thermodynamic, economic, and sensitivity analysis of salt gradient solar pond (SGSP) integrated with a low-temperature multi effect desalination (MED): Case study, Iran. (October 2021) - Masoud Parsa, Seyed; Majidniya, Mahdi; Alawee, Wissam.H.; Dhahad, Hayder A.; Muhammad Ali, Hafiz; Afrand, Masoud; Amidpour, Majid
Highlights: Feasibility investigation of integrating MED with SGSP is conducted for the first time for southern part of Iran. The highest and lowest productivity with 35, 484 and 71, 340 Liter/day are determined in June and December respectively. Detail construction cost of SGSP such as excavation, salt price, lining, transportation of soil/salt calculated based PBO. Sensitivity analysis is performed to determine the effects of economic parameters on the system. Effect of salt price in different scenarios is examined for the system. Abstract: Integration of a salt-gradient solar pond (SGSP) with multi-effect-desalination (MED) system for southern part of Iran is in present study. The proposed system was evaluated from thermodynamic and economic standpoints. Also, sensitivity analysis based on the important parameters of the system is performed. Economic analysis is performed for the first time based on the Iran's Plan and Budget Organization (PBO) price lists and local suppliers. Annual productivity of the proposed system for each month was evaluated and overall productivity of the system throughout a year calculated by about 20, 000 m 3 /year. The economic results indicated that the period of return (POR) of the intended system is around 6 years. The solar pond construction costs such as excavation, transportation, salt and lining, were considered based on the local prices (Bandar Abbas city) and PBO. The cost of constructing a solar pond was evaluated about 12 $/m 2 . Also, sensitivity analysis was elucidated to realize the effects of salt price and transportation cost on the system. Finally, the results showed that by reducing the salt price and eventually considering it's for free, POR will be reduced by about 45%, while by considering transportation cost equal to zero, POR will be reduced by about 25%.